Kepemimpinan dan Pengawasan terhadap Disiplin Kerja Karyawan - Markus Markus (Journal of Management and Bussines (JOMB), 2021)
This study aimed to determine the positive and significant relationship, a) leadership to work discipline, b) supervision to work discipline; c) leadership and supervision of work discipline. Data collection method used the questionnaire. The population of all employees of PT. Satria Mayangkara Sejahtera Lahat as many as 52 people and a sample of 52 people using the census method. The results showed that partially the leadership variable (X1) 5.567>2.009 was significant 0.000 <0.05, there was a significant influence of the leadership variable on work discipline. Supervision variable (X2) 15,734> 2,009, significant 0.000 <0.05, there is a significant effect of supervision on work discipline. Simultaneously 209,708>3,19 significant 0.000<0.05. In conclusion, the leadership variable, the supervisory variable and simultaneously the leadership and supervision variables have a significant influence on the work discipline variable of PT. Satria Mayangkara Prosperous. Keywords: Work Discipline, Leadership, Supervision